Monitoring workload in elite female basketball players during the in-season phase: Weekly fluctuations and effect of playing time - Paulauskas, H.; Kreivyte, R.; Scanlan, A. T.; Moreira, A.; Siupsinskas, L.; Conte, D. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To assess the weekly fluctuations in workload and differences in workload according to playing time in elite female basketball players. Methods: A total of 29 female basketball players (mean [SD] age 21 [5] y, stature 181 [7] cm, body mass 71 [7] kg, playing experience 12 [5] y) belonging to the 7 women`s basketball teams competing in the first-division Lithuanian Women`s Basketball League were recruited. Individualized training loads (TLs) and game loads (GLs) were assessed using the session rating of perceived exertion after each training session and game during the entire in-season phase (24 wk). Percentage changes in total weekly TL (weekly TL+GL), weekly TL, weekly GL, chronic workload, acute:chronic workload ratio, training monotony, and training strain were calculated. Mixed linear models were used to assess differences for each dependent variable, with playing time (low vs high) used as fixed factor and subject, week, and team as random factors. Results: The highest changes in total weekly TL, weekly TL, and acute:chronic workload ratio were evident in week 13 (47%, 120%, and 49%, respectively). Chronic workload showed weekly changes =10%, whereas monotony and training strain registered highest fluctuations in weeks 17 (34%) and 15 (59%), respectively. A statistically significant difference in GL was evident between players completing low and high playing times (P=.026, moderate), whereas no significant differences (P>.05) were found for all other dependent variables. Conclusions: Coaches of elite women`s basketball teams should monitor weekly changes in workload during the in-season phase to identify weeks that may predispose players to unwanted spikes and adjust player workload according to playing time.